Dynamic models of the roundwood market in Finland - Pentti Forsman; Tarja Heinonen (Bank of Finland, 1988)
We contribute to the discussion of the reasons why the supply of roundwood has lagged behind the growth of forests since the early 1970s. Our dynamic models of the roundwood market provide some evidence that the very low level of the real interest rate is an important reason for the sluggishness of fellings in private forests.
URN:NBN:fi:bof-201908051338
Keywords: 330